Comparative Analysis of Clinical Characteristics and Antimicrobial Resistance Between Acinetobacter baumannii and Other Acinetobacter Species - Si-Ho Kim; Seok Jun Mun (Pathogens)
Acinetobacter species are major pathogens responsible for hospital-acquired infections. This study aimed to compare the clinical characteristics, outcomes, and antimicrobial resistance between Acinetobacter baumannii (AB) and non-baumannii Acinetobacter (NBA) species. In this retrospective cohort study, we analyzed data from adult patients (aged 18 or older) with Acinetobacter bacteremia treated at two tertiary hospitals from July 2020 to November 2023. Among 260 cases of Acinetobacter bacteremia, 42 (16.2%) involved NBA species. The AB group exhibited higher antimicrobial resistance rates across all tested agents, except for minocycline. Female patients, younger patients, and those with catheter-related infections were more commonly observed in the NBA group than in the AB group, while pneumonia and septic shock were more prevalent in the AB group. In a multivariable analysis of 30-day mortality, factors associated with higher mortality included moderate to severe liver disease, chronic kidney disease, carbapenem resistance, septic shock, and higher Pitt Bacteremia Scores. When stratified by carbapenem resistance (CR) status, only CR-AB exhibited significantly lower 30-day survival rate (33.4%) compared to that of the other groups (non-CR-NBA, 77.3%; CR-NBA, 77.8%; non-CR-AB, 90.1%; p < 0.001). Our findings highlight distinct clinical differences between AB and NBA bacteremia cases; however, the mortality rate for non-CR-AB was comparable to that observed in NBA bacteremia.